EXAGGERATION OF TYPE 2 DIABETES DUE TO CAFFEINE-NICOTINE CO-ADMINISTRATION: A STUDY IN RATS - Kumbhar, Subhash T.; Une, Hemant D.; Joshi, Anagha M.; Wangikar, Pralhad B. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: This study evaluated the toxic effect of simultaneously injected normal doses of caffeine and nicotine in diabetic lab animals. Methods: A study was conducted for three weeks in seven rat groups (n=6); viz. first non-diabetic group treated with caffeine (20 mg/kg, ip) twice daily, second with nicotine (0.4 mg/kg, ip) twice daily and third with both treatments simultaneously; whereas other three groups treated in the same way but inducing diabetes; and employing the seventh group as diabetic control. Type 2 diabetes was induced by high fatty diet prior for two weeks and a single streptozotocin injection on 1th day of study in all diabetic groups. Blood and urine samples were collected weekly to estimate blood parameters. Animals were sacrificed, and organs were collected for histopathology analysis. Results: Most blood parameters showed a rapid increase in diabetes in co-addiction group compared with their single addiction or non-addiction control groups. Caffeine-nicotine co-addiction group showed about 60-80 mg/dl (p<0.05) rise in serum glucose, 15-20 U/l in AST (p<0.01), 80-100 U/l in ALT (p<0.01), 20-30 mg/dl in Urea (p<0.01), 02 mg/dl in creatinine (p<0.05), 12-15 mg/dl (p<0.01) in LDL-C, 6-9 mg/dl in VLDL-C (p<0.01) and 60-90 mg/dl in TC levels (p<0.01) when compared with non-addicted diabetic control. There was a significant reduction in HDL-C (p<0.01) while the less significant rise in triglycerides in the case of co-addiction as compared to non-addiction diabetic control group. Histopathology results exhibited moderate to severe tissue damage in agreement with clinical biochemistry results. Conclusion: Nicotine-caffeine co-addiction harms exceptionally more in type 2 diabetes greater than their single addiction or non-addiction.